As fronteiras de uma Universidade: o município de Realeza/PR e a instalação do Campus da Universidade Federal Fronteira Sul (UFFS) - Nichterwitz, Fernanda (2017)
The purpose of this study is to investigate the creation and installation of a campus of the Federal University of Southern Frontier (UFFS) in Realeza, State of Parana, Brazil. Therefore, some data for this study were collected from a series of interviews with a group of members that participated in the process that led to the creation of UFFS (besides students and professors) as well as from official documents dated from 2002 to 2015. This study aims to understand public policies for higher education in the Cardoso and Lula administrations related to the expansion and inland settlement of federal universities in Brazil. It will be also demonstrated how those policies could stimulate a broad range of social movements from three states of the country (Rio Grande do Sul, Santa Catarina and Paraná) in order to unite and articulate the establishment of a new Brazilian university. Finally, our study deals with the foundation project of UFFS – focusing on its undergraduate programs, its processes for student admission and housing conditions – contrasting it with the modes of operation of the university after the start of its activities in Realeza and the arrival of newcomers to that town.